Perancangan sistem informasi penjualan cat nippon pada CV. Perdana Jakarta bebasis java netbeans - Putri Khairunnisa; Nahot Frastian; Siwi Puji Astuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
CV. Perdana is a leading distributor that sells various types of paints with various brands located on Jl. Raya Jatinegara Barat, Jatinegara-East Jakarta. CV. Perdana has not utilized information system technology to support its sales data processing. CV. Perdana still uses paper to record reports and make notes on transactions that will buy paint in CV. Perdana, so data can be damaged, lost, and security is not guaranteed. To overcome this problem, in this study, the Nippon Paint Sales Information System was designed which aims to develop a manual paint sales system, using a computerized system on CV. Perdana, making it easier for employees to input data on incoming, outgoing, stock items, and sales recaps quickly, precisely and accurately, in order to streamline work time. The research technique used using the research method used in this design is a qualitative research method, namely research that uses an analytical method or conducts a direct investigative approach because researchers usually collect data by meeting face to face and interacting directly with people at the research site.